An artist of the floating world - Ishiguro, Kazuo, 1954- (Faber & Faber, 2016)
It is 1948. Japan is rebuilding her cities after the calamity of World War II, her people putting defeat behind them and looking to the future. The celebrated painter Masuji Ono fills his days attending to his garden, his house repairs, his two grown daughters and his grandson, and his evenings drinking with old associates in quiet lantern-lit bars. His should be a tranquil retirement. But as his memories continually return to the past - to a life and a career deeply touched by the rise of Japanese militarism - a dark shadow begins to grow over his serenity.